Prolactin promotes proliferation of germinal center B cells, formation of plasma cells, and elevated levels of IgG3 anti-dsDNA autoantibodies - Carreón-Talavera, Ricardo; Santana-Sánchez, Paola; Fuentes-Pananá, Ezequiel Moisés; Legorreta-Haquet, María Victoria; Chávez-Sánchez, Luis; Gorocica-Rosete, Patricia Sofia; Chávez-Rueda, Adriana Karina (Frontiers in Immunology, 2022)
Systemic lupus erythematosus (SLE) mainly affects females at reproductive age, which has been associated with hormones, such as prolactin (PRL). Different studies suggest that PRL exacerbates the clinical manifestations of SLE both in patients and in mouse models (e.g., the MRL/lpr strain), increasing the production of autoantibodies, which can be deposited as immune complexes and trigger inflammation and damage to different tissues. The objective of this work was to explore the potential mechanisms by which PRL increases the concentration of self-reactive antibodies in the MRL/lpr SLE model. To this end, we determined the role of PRL on the activation and proliferation of germinal center B cells (B-GCs) and their differentiation into antibody-secreting cells (ASCs). We show that the absolute number and percentage of B-GCs were significantly increased by PRL in vivo or upon in vitro treatment with anti-IgM and anti-CD40 antibodies and PRL. The augmented B-GC numbers correlated with enhanced proliferation, but we did not observe enhanced expression of CD80 and CD86 activation markers or the BCL6 transcription factor, arguing against a more effective differentiation. Nevertheless, we observed enhanced phosphorylation of STAT1, secretion of IL-6, expression of IRF4, numbers of ASCs, and levels of IgG3 antibodies directed against dsDNA. Altogether, these results support the hypothesis that a PRL-mediated expansion of B-GCs yields more self-reactive ASCs, potentially explaining the pathogenic immune complexes that steadily lead to tissue damage during SLE.